Respostas
respondido por:
2
{3x+y=12
{2x+3y=15
3x+y=12
y=12-3x
Substituindo na 2º equação:
2x+3y=15
2x+3(12-3x)=15
2x+37-9x=15
-7x=15-36
-7x=-21
x=3
Substituindo na 1º equação:
y=12-3x
y=12-3.3
y=12-9
y=3
Espero ter ajudado!
{2x+3y=15
3x+y=12
y=12-3x
Substituindo na 2º equação:
2x+3y=15
2x+3(12-3x)=15
2x+37-9x=15
-7x=15-36
-7x=-21
x=3
Substituindo na 1º equação:
y=12-3x
y=12-3.3
y=12-9
y=3
Espero ter ajudado!
larryzinha85:
obrigada! ♡
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás